Recent development on sustainable biodiesel production using sewage sludge - Srivastava N.; Srivastava M.; Gupta V.K.; Manikanta A.; Mishra K.; Singh S.; Singh S.; Ramteke P.W.; Mishra P.K. (My University, 2025)
Biodiesel as a renewable energy is an important alternative to biofuels in current scenario to explore green energy sources. It is well known that the major cost involved in biodiesel production technology is dependent upon the used feedstock. This review presents an overview of biodiesel production using municipal sewage sludge as a cost-effective substrate. Municipal sewage sludge which possesses high lipid content with zero cost availability can meet the characteristics of a potential feedstock to produce biodiesel. Different types of substrates based processes to produce biodiesel have been also explored in brief. In addition, limitations of the existing process technology for biodiesel production with sustainable solutions have been also discussed. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.